Perlindungan Hukum Terhadap Penyalahgunaan Data Pribadi Dalam Transaksi Pinjaman Online - Madrim; Nurhidayat (JOURNAL SAINS STUDENT RESEARCH, 2023)
In online loan application services, many people have complained about the issue of the dissemination of personal data carried out by providers of online loans without notice and without permission from the owner. In this regard, it is important to review legal protection of borrowers' personal data in online loan application services, and sanctions for violating personal data. The purpose of this paper is to examine the legal protection of borrowers' personal data in online loan application services. The method used in this paper is a normative legal method with a statutory approach and a factual approach. The results of the study show that legal protection and sanctions for violations of personal data are regulated in Law No. 11 of 2008 and amendments to Information and Electronic Transactions along with implementing regulations, but specifically regarding legal protection and sanctions for violating personal data in online loan services are listed in the Financial Services Authority Regulation No. 77/POJK.01 2016 concerning Information Technology-Based Money Lending and Borrowing Services, which is stated in Article 26 that the organizer is responsible for maintaining confidentiality, integrity and availability of the user's personal data and in its utilization must obtain the approval of the owner of personal data unless specified otherwise by the provisions legislation. Sanctions for violating personal data refer to Article 47 section (1), namely administrative sanctions in the form of written warnings, fines, obligations to pay certain amounts of money, restrictions on business activities, and revocation of licenses.